Effect of Static Contraction on Pain Reduction in Postpartum Mothers with Perineal Tears - Nurhayati, Rini; Rahmawati, Nurul Aini; Yulianti, Atika (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Static contraction is a form of contraction exercise in muscles that uses static principles, where the muscles trained will experience changes in muscle length while the joints remain in a static or stationary state. Static contractions are useful for reducing pain, one of which is for perineal pain due to tearing during childbirth. Perineal pain is pain felt in the genital area associated with lacerations or tears in the perineum. The purpose of this study was to determine the effect of giving static contraction exercises on reducing pain in spontaneous birth postpartum mothers with perineal tears. Method: This study utilized a quasi-experimental design involving 20 respondents, who were divided into treatment and control groups. The treatment group was given static contractions 2 times a day and the control group was given stretching 2 times, the pain level was measured using NRS (Numerical Rating Scale). Results: based on the results of the paired t test for the treatment group showed a p value = 0.000 while in the control group showed a p value = 0.000 which indicates an effect. The independent t test found a value of p = 0.001 indicating a difference in influence between the treatment group and the control group. Conclusion: there is an effect of giving static contraction exercises on reducing pain in spontaneous birth postpartum mothers with perineal tears. The results of this study can be used as a reference in conducting subsequent research on larger samples and populations. Pendahuluan: Statik Kontraksi adalah suatu bentuk latihan kontraksi pada otot yang menggunakan prinsip statis, dimana otot yang dilatih akan mengalami perubahan panjang otot sedangkan sendinya tetap pada keadaan statis atau diam. Statik kontraksi bermanfaat untuk mengurangi nyeri, salah satunya adalah untuk nyeri perineum akibat robekan pada saat proses melahirkan. Nyeri perineum merupakan nyeri yang dirasakan pada area genital yang berhubungan dengan adanya laserasi atau robekan pada perineum. Metode: Penelitian ini menggunakan desain penelitian quasi eksperimental dengan sampel yang berjumlah 20 responden yang dibagi menjadi kelompok perlakuan dan kelompok kontrol. Kelompok perlakuan diberikan statik kontraksi 2 kali sehari dan kelompok kontrol diberikan stretching 2 kali, tingakat nyeri diukur menggunkan NRS (Numerical Rating Scale). Hasil: berdasarkan uji paired t test pada kelompok perlakuan didapatkan nilai p = 0,000 dan pada kelompok kontrol didapatkan nilai p = 0,000 yang menandakan adanya pengaruh. Sedangkan pada uji independent t test didapatkan niali p=0,001 yang menandakan bahwa adanya perbedaan pengaruh antara kelompok perlakuan dan kelompok kontrol. Simpulan: terdapat pengaruh pemberian latihan statik kontraksi terhadap penurunan nyeri pada ibu post partum kelahiran spontan dengan robekan perineum.